Acordo de não persecução cível (ANPC) como instrumento da justiça restaurativa no Direito Administrativo sancionador: desafios e perspectivas - Martins, Debora Maria (2025)
Restorative Justice (JR) seeks to build more humane and effective solutions to conflicts, promoting dialogue, mutual understanding, and the restoration of harmony in society, typically within the scope of Criminal Law. However, it is important to reflect on its application in other legal areas, such as Administrative Sanctioning Law, which regulates infractions committed within public administration and the sanctions applicable to those who violate administrative rules. The Civil Non-Prosecution Agreement (ANPC) in Administrative Improbity was chosen as the subject of this study, as it represents part of the consensualization of Public Administration and the overcoming of the traditional model of access to justice. Once the subject was defined, the question arose as to what measures could be taken to ensure a more effective application of this instrument. To answer this question, a qualitative documentary research was conducted, as it investigates aspects of JR within the administrative context. It is also classified as deductive, as it starts from general theories of JR in the criminal sphere to draw specific conclusions about its application in the administrative field. It was concluded, in summary, that Brazilian regulation still presents gaps, especially in defining the role of the facilitator and the clarity of community participation and the Guarantee of Rights Network. There is also a need for clearer criteria for case referrals, as the application of restorative programs depends on the discretion of judges. Furthermore, the model of Public Administration participation in restorative processes needs to be clearer, considering the complexity of institutional relations and local needs. Proposals were presented for shared opinions between immediate leadership and the corrective body during the hearing of the federative entity in the ANPC, as well as the creation of limits for restitution to the public treasury, aiming to increase the effectiveness and transparency of these processes.